The competence of EFL teachers in mastering genre based texts - Mahfud, Rois (Journal on English as a Foreign Language (JEFL), 2011)
This study aimed to find out the junior high school English teachersâ competence in mastering genre-based texts. The study was conducted to 13 English teachers of Junior High Schools in the districts of Kahayan Hilir, Maliku, and Jabiren Raya in Pulang Pisau Regency.Â  The data were obtained from test and questionnnaire. The result of the test shows that the teachersâ mastery in all genre-based texts was at the âfairâ level with 65.38. The average score in each genre varied with 79.23 (good) for recount text; 68.46 (fair) for procedural text; 65.77 (fair) for descriptive text; 64.23 (poor) for narrative text; and 46.54 (very poor) for report text. Meanwhile, the result of the questionnaire revealed that there was no training for teachers on genre-based texts. The finding of this study reccommends the need of training in mastering genre based texts for Junior High School teachers for better studentsâ achievement in mastering genre-based text and for better preparation for National Examination. Â